2016
DOI: 10.1097/brs.0000000000001396
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Surgical Treatment of Lower Back Pain Among Spine Surgeons in the United States

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Prior research has demonstrated a great degree of variation both in terms of indications for spine surgical intervention as well as the types of procedures performed for a wide range of similar spinal disorders [2,5,11,15,17,20,21]. Much of this variation involves the use of high-intensity, expensive surgical interventions such as instrumented interbody fusions [2,5,15,17,21].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has demonstrated a great degree of variation both in terms of indications for spine surgical intervention as well as the types of procedures performed for a wide range of similar spinal disorders [2,5,11,15,17,20,21]. Much of this variation involves the use of high-intensity, expensive surgical interventions such as instrumented interbody fusions [2,5,15,17,21].…”
Section: Introductionmentioning
confidence: 99%
“…Rather than patient level factors, geographic variations in MNT prior to spine surgery may stem in large part from the lack of consensus among providers surrounding the most efficacious nonoperative therapies or the optimal duration of conservative trial periods. In a study of 445 US spine surgeons given surveys designed to assess their treatment patterns of low back pain, Lubelski et al 27 found roughly 75% disagreement between providers on their treatment approach. This disagreement was most pronounced in the Southwest and weakest in the Midwest.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these instrumented techniques of fusion are; instrumented posterolateral fusion (PLF), anterolateral inter body fusion (ALIF), posterior inter body fusion (PLIF), Transforaminal inter body fusion (TLIF). [7][8][9][10] Asides the posterolateral fusion, the other techniques employ the use of interbody cages for interbody fusions. Instrumented Posterolateral fusions (PLF) can be done alone as a procedure and has been shown to be effective in treating such conditions or can be combined with the various types of interbody fusion techniques.…”
Section: Introductionmentioning
confidence: 99%